1993
DOI: 10.1213/00000539-199376060-00002
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Different Intravascular Volume Therapies on Platelet Function in Patients Undergoing Cardiopulmonary Bypass

Abstract: The influence of four different kinds of intravascular volume replacement on platelet function was investigated in 60 patients undergoing elective aortocoronary bypass grafting using cardiopulmonary bypass (CPB). In a randomized sequence, high-molecular weight hydroxyethyl starch solution (HMW-HES, mean molecular weight [Mw] 450,000 d), low-molecular weight HES (LMW-HES, Mw 200,000 d), 3.5% gelatin or 5% albumin were infused preoperatively to double reduced filling pressure (pulmonary capillary wedge pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(29 citation statements)
references
References 0 publications
0
26
0
3
Order By: Relevance
“…For pigs there have been no studies formally comparing the above-noted three intravascular volume expanders. For humans one study compared albumin, HES with an average MW of 200,000, and HES with an average MW of 450,000 (Boldt et al, 1993). In this study with 75 cardiac surgery patients, use of the higher MW HES was associated with significantly higher blood losses during the first postoperative day when compared with controls and other treatments.…”
Section: Discussionmentioning
confidence: 85%
“…For pigs there have been no studies formally comparing the above-noted three intravascular volume expanders. For humans one study compared albumin, HES with an average MW of 200,000, and HES with an average MW of 450,000 (Boldt et al, 1993). In this study with 75 cardiac surgery patients, use of the higher MW HES was associated with significantly higher blood losses during the first postoperative day when compared with controls and other treatments.…”
Section: Discussionmentioning
confidence: 85%
“…Large HES molecules interfere with fibrinogen, coagulation factor VIII, and von Willebrand factor, and their negligible effect on coagulation is more than can be expected as a result of hemodilution (Omar et al 1999). HES also promotes platelet dysfunction by disturbing platelet aggregation in vitro (Boldt et al 1993). In studies assessing viscoelastic properties of whole blood, HES has been consistently demonstrated to disturb fibrin formation and to reduce clot firmness Kuitunen 1998, Boldt et al 2007).…”
Section: Coagulation Effects Of Hydroxyethyl Starchesmentioning
confidence: 99%
“…The effects of hydroxyethyl starches on hemostasis have been studied by many authors 63,67,90,91 . Hydroxyethyl starches with a high in vivo Mw should be distinguished from other hydroxyethyl starches.…”
Section: Hydroxyethyl Starchesmentioning
confidence: 99%